2018
DOI: 10.1093/jas/sky419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplying omega-3 polyunsaturated fatty acids to gilts after weaning on metabolism and ovarian gene expression1

Abstract: Omega-3 PUFA may benefit sow reproductive performance, but effects on weaned gilts are unknown. This study evaluated the effects of supplementing omega-3 PUFA to gilts after weaning on growth, metabolic markers, and gene expression of steroidogenic enzymes and hormone receptors. For 52 d, gilts in the control group were fed 100 g/d of regular diets, whereas gilts in the omega-3 group were fed 75 g/d of such diets plus 25 g/d of the microalgae Schizochytium sp. (3.5 g/d of omega-3 PUFA; n = 8 gilts/group). Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Although all of our diet reversals were able to at least partially restore HFD-induced gene dysregulation, each of the three dietary interventions also invoked a unique ovarian gene expression profile, highlighting the impact diet has on ovarian gene expression. Others have also shown that changes in diet alter ovarian gene expression including HFDs (69), omega-3 FA supplementation (70), and maternal low protein diets (71). Interestingly, we have previously shown that HFD alters ovarian gene expression regardless of obesity (7).…”
Section: Discussionmentioning
confidence: 65%
“…Although all of our diet reversals were able to at least partially restore HFD-induced gene dysregulation, each of the three dietary interventions also invoked a unique ovarian gene expression profile, highlighting the impact diet has on ovarian gene expression. Others have also shown that changes in diet alter ovarian gene expression including HFDs (69), omega-3 FA supplementation (70), and maternal low protein diets (71). Interestingly, we have previously shown that HFD alters ovarian gene expression regardless of obesity (7).…”
Section: Discussionmentioning
confidence: 65%
“…In animals fed restricted food for a considerable amount of time, the number of dominant follicles in the ovaries was minimal, resulting in low estrogen levels. Low cholesterol levels in this study also caused low estrogen levels because total cholesterol influences ovulatory steroidogenesis [ 34 ]. A previous study found that low blood GLU and cholesterol levels reduce LH pulses during follicular development, and LH functions as a factor in the formation of androgen hormones in granulosa cells to be converted into estrogen hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize, however, that diet can affect ovarian function. For example, low protein intake reduces mouse primordial follicle activation, and omega-3 polyunsaturated fatty acids supplements alter mouse follicular cell gene expression [50, 51]. Thus, systematically determining the effect of specific diets on periovarian adipose tissue architecture and lipid profiles could be informative.…”
Section: Discussionmentioning
confidence: 99%